Changes in chocolate crystallization are influenced by type and amount of introduced filling lipids. Issue 11 (15th October 2015) - Rothkopf, Isabell; Danzl, Wolfgang
Abstract : Filled chocolates are particularly susceptible to quality loss due to oil migration. Since the fillings are often softer than the chocolate coatings, the filling lipids can function as an activator for diffusion processes with the formation of fat bloom as a consequence. Filling lipids can merge with chocolate during production or storage. However, in most studies concerning crystallization or migration cocoa butter and hazelnut oil were analyzed, investigations on chocolate are rare. To cover a broad variety of fillings, dark chocolate was blended with hazelnut oil, butterfat, and coconut oil and crystallization was analyzed. All investigated lipids reduced the solid fat content to the same extend. However, crystallization behavior of the blended samples differed. Hazelnut oil accelerated crystallization rate and did not affect crystallization time, while butterfat reduced crystallization rate and time. The effect of coconut oil addition was in between those of hazelnut oil and butterfat. Nucleation and crystal growth rate, which affect the crystallization speed, have been shown to be affected by the type of filling lipid. Additionally, there is evidence that crystal transformation during crystallization is also affected by filling lipids. Practical applications : Based on the results of this study, manufacturers of filled chocolate products may adapt their processing parameters such as temperature and retention time in the cooling tunnel accordingly. The analytical methods may be used to control the production of confectionery and to determine filling fat concentrations in the chocolate shells of freshly produced pralines. As different filling lipids in small contents cause similar softening of chocolate shells, the solid fat content (SFC) of chocolate is an appropriate method to control filling lipid migration into chocolate. Isothermal crystallization of non‐tempered samples shown as solid fat content (SFC) versus time indicate that hazelnut oil has a less retarding effect on crystallization than butterfat and the effect of coconut oil is in between, but closer to hazelnut oil. Abstract : Isothermal crystallization of non‐tempered samples shown as solid fat content (SFC) versus time indicate that hazelnut oil has a less retarding effect on crystallization than butterfat and the effect of coconut oil is in between, but closer to hazelnut oil.